Zen of cloud learning cloud computing by examples on microsoft azure - Bai, Haishi (CRC Press, Taylor & Francis Group, 2015)
"This book presents cloud computing, using a series of practical and fun examples. It provides comprehensive coverage of Windows Azure cloud platform, the theories behind cloud computing, as well as guidance and best practices in designing cloud-based applications. It can serve as a reference for cloud system developers, architects, and IT professionals. It is also suitable for use in instructional settings"